Respostas
respondido por:
2
(x - 10)² = 9
x² - 20x + 100 = 9
x² - 20x + 100 - 9 =0
x² - 20x + 91 = 0
Δ = (-20)² - 4(1)(91)
Δ = 400 - 364
Δ = 36
√Δ = 6
x1 = (20 + 6)/2 = 13
x2 = (20 - 6)/2 = 7
S = {x ∈ R / x = ∈7 ou x = 13}
Espero ter ajudado.
x² - 20x + 100 = 9
x² - 20x + 100 - 9 =0
x² - 20x + 91 = 0
Δ = (-20)² - 4(1)(91)
Δ = 400 - 364
Δ = 36
√Δ = 6
x1 = (20 + 6)/2 = 13
x2 = (20 - 6)/2 = 7
S = {x ∈ R / x = ∈7 ou x = 13}
Espero ter ajudado.
Perguntas similares
7 anos atrás
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás